Biosorption efficiency of FE(II), CU(II), PB(II) and ZN(II) from aqueous solution by living Pleurotus ostreatus / Arbanah Muhammad - Muhammad, Arbanah (2013)
Heavy metal ions such as Fe(II), Cu(II), Pb(II) and Zn(II) are pollutant mostly present in the wastewater and should be removed due to their potential hazards. However, the conventional removals o f heavy metals have technical and economical constraints. In this present study, the biosorption using fimgus, Pleurotus ostreatus(P.ostreatus) was introduced to remove heavy metals from aqueous solution. The objective of the present study was to evaluate and characterize the potential application o f P.ostreatus as alternative biosorbent in the removal of Fe(II), Cu(II), Pb(II) and Zn(II), to investigate the effect of pH, temperature, agitation speed and P.ostreatus dosage on biosorption efficiency and to assess the biosorption efficiency of P.ostreatus on multimetal ion solution and liquid laboratory chemical waste. The scope of this study was set up for pH (2, 3, 4, 5, 6), temperature (20, 25, 30, 35, 40°C), agitation speed (50, 100, 150, 200, 250 rpm) and P.ostreatus dosage (2, 4, 6, 8, 10 g/L). The initial and final concentrations of heavy metals in aqueous solution were evaluated using Atomic Absorption Spectroscopy (AAS) and the best operating conditions were achieved at the highest biosorption efficiency, E(%). It was found that, the maximum biosorption efficiency was observed at pH 6 (Fe(II); Cu(II)), pH 5; (Pb(II)) and pH 4 (Zn(II). The best operating conditions were found to be at 25°C, 150 rpm, 8 g/L P.ostreatus dosage and one hour contact time. The removal of heavy metal from multi-metal ion solution and chemical waste was lower than single metal ion solution. It was showed that about 69.60, 46.46, 36.81 and 17.38% of Fe(II), Cu(II), Pb(II) and Zn(II) were removed from chemical waste. The Fourier Transform Infrared (FTIR) analysis proved the involvement of carboxylic(-COOH) and amide(-NH2) groups on the cell wall of P.ostreatus during the biosorption. The current study validates P.ostreatus as a potential and valuable biosorbent in heavy metals removal from aqueous solution.